SnapFib: An easy build Arduino based tabletop prototype for thin film deposition by Successive Ionic Layer Adsorption and Reaction method - Sen Gupta, Ashoke Kumar; Adnan, Abu; Bhattacharjee, Shantanu; Das, Nipu Kumar; Matin, M.A.; Quamruzzaman, Muhammad (HardwareX, 2022)
[Display omitted] Non-vacuum-based techniques are suitable for thin-film deposition with precision stoichiometric control. Among those, the Successive Ionic Layer Adsorption and Reaction (SILAR) method is gaining popularity for its aqueous-based almost room temperature deposition option. This method has many advantages, including the ability to control the elemental composition and stoichiometry of precursors. It is also suitable for large-area deposition. It has many runtime parameters, e.g., the number of cycles, dip time, rinse time, etc., that control the quantitative and qualitative physical properties of the deposited film. But manually controlling all these parameters for the whole process is very difficult and cumbersome. Although there are several reports published on this similar type of home-built prototype, for fast, accurate, and economically affordable deposition operations, we need to develop a machine that maintains all the properties of the SILAR process and can be made using cheap technologies. Here we report the SnapFib, a cost-effective automated tabletop prototype machine that is easy to build for thin-film deposition on soda-lime glass substrates by the SILAR method without almost any human intervention. SnapFib is built using linear actuators, an ATmega328P (a microcontroller available on Arduino boards), and some other parts collected from laboratory sites. The whole firmware needed for this device has been developed and maintained using the Arduino IDE (Integrated Development Environment). All required functional features and control parameters are encoded in the microcontroller firmware. The construction cost of this prototype is around 600 USD. We validated our construction through XRD (X-ray Diffraction) and FESEM (Field Emission Scanning Electron Microscope) characterizations of thin films that were deposited by SnapFib. Since this is built under the CC-BY license, students and researchers can freely perform and validate their experiments and modify the hardware and software as required. With how easy it is to make and how much it costs; we hope that many thin-film deposition labs will quickly start using SnapFib as an added benefit.